How research institutions can make the best of scandals – once they become unavoidable. (20th December 2022) - Grolleau, Gilles; Mzoughi, Naoufel
Abstract : We posit that, once scandals become unavoidable, they can be considered for transformation into opportunities for research institutions, scientific communities and science regulators to implement in-depth changes and policies they would otherwise oppose. Research institutions and scientific communities can take advantage of scandals by participating proactively in constructing their consequences. We develop four mechanisms by which scandals can be used to bring positive change in research institutions and scientific communities. These are nullifying the high-status protection of almost untouchable researchers, 'resetting' the system that was conducive to scandals, changing the reference point upon which the entity is judged to emphasize progress and offering a learning opportunity to involved parties.